Comparative Analysis of Active Investment Strategies and the Buy-and-Hold Approach in Cryptocurrencies - Bušek, Jan-Jakub (2025)
The goal of this thesis is to compare simple trading strategies against the basic buy-and-hold approach, where one buys an asset and holds it without selling, mainly focusing on the S&P 500 and individual stocks. This approach may have been effective in the past, but current turbulent times, marked by global conflicts and widespread fear, raise questions about its viability. Is it still possible to find a safe space for our capital while also increasing its value in these market conditions? This thesis aims to address the question and explore the possibilities of active investment strategies while minimizing drawdowns and maximizing the potential return on investment. Apart from that, the thesis is focusing on maximizing the opportunities of the increased market volatility by using long and short strategies, in order to profit even in market drawdowns. The methodologies used include basic statistical techniques such as trend following, momentum, and ARIMA. All of these strategies were developed on cryptocurrencies, which are significantly more volatile but also have the potential for significantly higher returns compared to traditional stocks, ETFs, or bond markets.